ANALISIS KOMPARATIF USAHATANI JAGUNG LAHAN SAWAH DAN LAHAN KERING DI KABUPATEN SUMBAWA - Siti Nurwahidah (Universitas Muhammadiyah Purwokerto, 2014)
Development of corn commodity is still superior commodity in West Nusa Tenggara in general and Sumbawa in particular. Therefore, information on corn farming in different agrosystem (wet and dry lands) is needed. Research location was determined purposively. The research used t-test analysis, R/C ratio, production factors, cost, revenue and farming income to analyze data. It is done in Labangka district having great potential for dry land cultivation and Utan district that is corn production center in wet area. Result of the research indicated that average productivity of farming in wet land and dry land are 6,716 kg/ha and 6,092 kg/ha, respectively with t=48.375. Average farmer income in wet area and dry area are Rp.11,183,273 and Rp.10,479,762, respectively. R/C ratio corn farming in dry land = 4,6 and R/C ratio corn farming in wet land = 3.3. It indicates that profit of corn farming in dry land at rainy season is lower than profit of corn farming in wet land in dry season. Keywords: corn farming, dry land, wet land